The Lumbar Spine as a Dynamic Structure Depicted in Upright MRI. Issue 32 (August 2015) - Kubosch, David; Vicari, Marco; Siller, Alexander; Strohm, Peter C.; Kubosch, Eva J.; Knöller, Stefan; Hennig, Jürgen; Südkamp, Norbert P.; Izadpanah, Kaywan; Weisheng, Zhang.
<x xml:space="preserve">Abstract</x> Abstract Spinal canal stenosis is a dynamic phenomenon that becomes apparent during spinal loading. Current diagnostic procedures have considerable short comings in diagnosing the disease to full extend, as they are performed in supine situation. Upright MRI imaging might overcome this diagnostic gap. This study investigated the lumbar neuroforamenal diameter, spinal canal diameter, vertebral body translation, and vertebral body angles in 3 different body positions using upright MRI imaging. Fifteen subjects were enrolled in this study. A dynamic MRI in 3 different body positions (at 0° supine, 80° upright, and 80° upright + hyperlordosis posture) was taken using a 0.25 T open-configuration scanner equipped with a rotatable examination bed allowing a true standing MRI. The mean diameter of the neuroforamen at L5/S1 in 0° position was 8.4 mm on the right and 8.8 mm on the left, in 80° position 7.3 mm on the right and 7.2 mm on the left, and in 80° position with hyperlordosis 6.6 mm (P < 0.05) on the right and 6.1 mm on the left (P < 0.001). The mean area of the neuroforamen at L5/S1 in 0° position was 103.5 mm2 on the right and 105.0 mm2 on the left, in 80° position 92.5 mm2 on the right and 94.8 mm2 on the left, and in 80° position with hyperlordosis 81.9 mm2 on the right and 90.2 mm2 on the left. The mean volume of the spinal canal at the L5/S1 level in 0° position was 9770 mm3, in 80° position 10600 mm3, and in 80° position with hyperlordosis 9414 mm3. The mean intervertebral translation at level L5/S1 was 8.3 mm in 0° position, 9.9 mm in 80° position, and 10.1 mm in the 80° position with hyperlordosis. The lordosis angle at level L5/S1 was 49.4° in 0° position, 55.8° in 80° position, and 64.7 mm in the 80° position with hyperlordosis. Spinal canal stenosis is subject to a dynamic process, that can be displayed in upright MRI imaging. The range of anomalies is clinically relevant and dynamic positioning of the patient during MRI can provide essential diagnostic information which are not attainable with other methods.